Abdominal visceral fat accumulation measured by computed tomography associated with an increased risk of gallstone disease. Issue 8 (August 2015) - Sekine, Katsunori; Nagata, Naoyoshi; Sakamoto, Kayo; Arai, Tomohiro; Shimbo, Takuro; Shinozaki, Masafumi; Okubo, Hidetaka; Watanabe, Kazuhiro; Imbe, Koh; Mikami, Shintaro; Nozaki, Yuichi; Sakurai, Toshiyuki; et al.
Abstract Background and Aim Visceral adiposity is a strong determinant of insulin resistance, which decreases cholecystokinin response sensitivity, and increases cholesterol saturation in the gallbladder bile; thus, it potentially relates to gallstone disease development. We aimed to investigate whether visceral fat measured by computed tomography (CT) is a risk factor for gallstone disease. Methods A cohort of 717 participants undergoing CT and ultrasonography was analyzed. The associations between body mass index (BMI), visceral adipose tissue (VAT) area, subcutaneous adipose tissue (SAT) area, and gallstone disease were analyzed adjusted for age, sex, hypertension, diabetes, and dyslipidemia. Results In multivariate analysis, gallstone disease was significantly associated with VAT and SAT areas for both categorical data and trend (P for trend < 0.001, 0.009), but not body mass index (BMI). Among patients with BMI < 25, gallstone disease remained significantly associated with VAT area (P for trend 0.021) and SAT area (P for trend 0.005). Interactions between the obesity indices and being elderly on the risk of gallstone disease were found; specifically BMI (P = 0.005), SAT (P < 0.001), and VAT (P = 0.154). A significant association between all obesity indices and gallstone disease was seen in patients aged < 65 but not among those aged ≥ 65. However, no significant association was noted between the obesity indices and sex. Conclusions CT‐measured adipose tissue, rather than BMI, was a better predictor for risk of gallstone disease. This finding applies to younger people or even those with normal body weight, suggesting the importance of abdominal visceral fat accumulation in the development of gallstone disease.